Newly discovered orichalcum ingots from Mediterranean sea: Further investigation. (June 2021) - Caponetti, Eugenio; Armetta, Francesco; Brusca, Lorenzo; Ferrante, Marco; Chillura Martino, Delia; Saladino, Maria Luisa; Guastella, Dario; Chirco, Gabriella; Berrettoni, Mario; Zamponi, Silvia; Conti, Paolo; Tusa, Sebastiano
Highlights: New Orichalcum ingots discovery. Chemometric analysis to recognize similarities and differences between two discoveries. Provenience study through lead isotopes analysis. Abstract: In February 2016, 47 ingots were found in the seabed of Contrada Bulala (Gela, CL, Italy) near the site where 40 ingots had previously been recovered. The ingots composition was determined to be a Cu - Zn alloy, dated by the archaeologist to the VI century B.C. This specific alloy was then known as Orichalcum . From an archaeological point of view, the first question raised about the new discovery was whether the ingots of the first and the second excavations belonged to the same shipwreck. Following the previous study, an elemental analysis was performed on the ingots from the second finding by using ICP-OS and ICP-MS techniques. The chemometric treatment of the analytical results obtained on both sets, i.e. ingots from first and second discovery, confirms their similarity. Therefore, the two findings can be considered to belong to the same naval load. The lead isotopic ratios were determined on selected/representative ingots to improve the knowledge about this treasure. Results can provide information about probable location of the lead sources, that could be very useful for the reconstruction of the ancient trade routes in the Mediterranean Sea.